Pemanfaatan Media Sosial Instagram Untuk Media Promosi @aerostreet - Aprilia, Ivendriana; Yenny; Dhimam Abror (Journal Communication Specialist, 2023)
Online product marketing through social media can now be done through Instagram as a promotional tool or media. For this reason, this research was conducted to find out how the use of social media Instagram for online shop promotion media @aerostreet. In forming a promotional strategy through social media Instagram uses the Marketing Mix theory. This study uses qualitative methods, with data collection techniques in the form of documentation. The documents in this study are in the form of writing, photos, or pictures taken from the online store’s Instagram account @aerostreet. From the results of this study it can be concluded that the @aerostreet online store uses Instagram social media for promotional media using 9 Instagram features, uploading photos or videos, captions, comments, hashtags, likes, explore, Instagram stories, live Instagram, geotagging, and also uses Artists and Brand as promotional media in the use of Instagram.